Analysis of Mathematics Learning Independence During the COVID-19 Pandemic - Emilianus Jehadus; Asep Rosadi; Lana Sugiarti; Veronika Kladia Samul (South Sulawesi Education Development (SSED), 2024)
This study aims to describe independent mathematics learning during the COVID-19 pandemic among eighth-grade students at SMP Negeri 2 Langke Rembong. The research was motivated by a lack of student learning independence in online learning, as evidenced by low motivation and interest, which resulted in passive participation in virtual classes. This study employs a descriptive quantitative approach using a survey method. The population consists of all eighth-grade students at SMP Negeri 2 Langke Rembong, totaling 339 students. The sampling technique used was probability sampling with a simple random sampling method, resulting in a sample size of 77 students. The data collection instrument was a Likert-scale questionnaire distributed to students, measuring their mathematics learning independence during the COVID-19 pandemic. The collected data was analyzed using descriptive statistical analysis. The results indicate that eighth-grade students at SMP Negeri 2 Langke Rembong demonstrated a high level of learning independence in mathematics during online learning. Students exhibited strong independence in eight key indicators, including formulating learning objectives, selecting learning strategies, taking the initiative to learn with or without assistance, evaluating their own learning progress, constructing meaning, collaborating with others, diagnosing learning needs, selecting and utilizing resources, and exercising self-control.